APOBEC-induced cancer mutations are uniquely enriched in early replicating, gene dense, and active chromatin regions - Kazanov, Marat D. (Cell Rep, 2015)
An antiviral component of the human innate immune system - the APOBEC cytidine deaminases – was recently identified as a prominent source of mutations in cancers. Here, we investigated the distribution of APOBEC-induced mutations across the genomes of 119 breast and 24 lung cancer samples. While the rate of most mutations is known to be elevated in late replicating regions that are characterized by reduced chromatin accessibility and low gene density, we observed a marked enrichment of APOBEC mutations in early-replicating regions. This unusual mutagenesis profile may be associated with a higher propensity to form single-strand DNA substrates for APOBEC enzymes in early-replicating regions and should be accounted for in statistical analyses of cancer genome mutation catalogues aimed at understanding the mechanisms of carcinogenesis as well as highlighting genes that are significantly mutated in cancer.